Elucidation of the Impact of Lead Chloride on Growth Characteristics and Chlorophyll Content in Two Varieties of Sunflower (Helianthus annuus L.): Effect of Lead Chloride on Sunflower (Biological Sciences - PJSIR, 2026)
Lead (Pb) is one of the common environmental stressors around the globe. To assess the effects of lead chloride on growth and physiological attributes of two varieties (Hysun-33 and FH-701) of sunflower (Helianthus annuus L.), a pot experiment was laid down with different levels of lead chloride. Pb (50, 100 or 150 ppm PbCl2/Kg of soil) fed to soil significantly affected the growth traits and photosynthetic pigments as compared to control (0 ppm) in both the varieties. In present findings, exposure of high Pb levels induced reduction in biomass (fresh and dry weights), root and shoot length and leaf traits (leaves per plant, leaf area, leaf lengths and leaf width) with the maximum readings found in control. The plant biomass decreased non-linearly in plants with higher doses of Pb. Root and shoot lengths declined up to 36.2 and 30.34% in Hysun-33, respectively. However, leaf length, leaf width, leaf area and leaves per plant reduced from 1.5 to 33%, 3.8 to 22.1%, 5.2 to 48.2% and 17.5 to 45.6% in Hysun-33, while 5.8 to 20.5%, 6.8 to 28.8%, 12.3 to 43.5% and 15.5 to 40% in FH-701 respectively.   All photosynthetic (main and accessory) pigments showed a reduction proportional to the increased Pb levels. The maximum drop in chlorophyll a (24.1%), chlorophyll b (42.07%), total chlorophyll (28.26%) and carotenoids (15.82%) was observed in FH-701 at highest Pb levels. The phytotoxicity of Pb on sunflower was dependent on varietal potential of sunflower and Pb   concentration.